The Need to Educate Social Entrepreneurship in the Opinion of Academic Teachers from Poland and Ukraine - Maria PŁONKA; Jolanta STANIENDA; Adam BIGOS (Communications of International Proceedings, 2021)
Background: New socio-economic conditions resulting from the consequences of the fourth industrial revolution and additionally caused by the effects of the COVID 19 pandemic imply the need to sensitize society to social problems and the need to educate new generation social entrepreneurs.The aim of the research is to find out the opinions of academic teachers from Poland and Ukraine on knowledge, development potential, education needs, level of education, preferred values ​​and support for social entrepreneurship, as well as differences in opinions between respondents from both countries. Methods: The research tool was a CAWI (Computer Assisted Web Interview) survey with the same content, conducted among academic teachers from Poland and Ukraine.This article fills the theoretical and cognitive gap concerning the survey of respondents' opinions on various aspects of developing and educating social entrepreneurship. The results of the study were summarized by means of a differential. Results: Comparing the results of the survey, both Polish and Ukrainian respondents see the need for development and education in the area of ​​social entrepreneurship, although respondents from Ukraine see it to a greater extent than respondents from Poland. Significant differences of views concerned: the assessment of the level of current knowledge on social entrepreneurship, the development potential of social entrepreneurship, the need to educate social entrepreneurship in contemporary socio-economic conditions, the level at which this should be educated, values ​​that should be shaped in the process of teaching social entrepreneurship and expectations regarding institutional support for social entrepreneurship. Conclusion: The article fills the theoretical and cognitive gap regarding the opinion poll on the need to educate social entrepreneurship. Another cognitive gap is the fact that Ukraine, unlike Poland and the European Union countries, is a country that is little explored in research on social entrepreneurship. The results of the research may support their deepening and implementation into educational programs.
Keywords: Social Entrepreneurship; Social Entrepreneur; Poland; Ukraine; COVID19; Education